(3GdLeGf aj eNJUQ CNHGQ GdReGfs - (3CHh YHO Gddg eMeO Hf Ydj Hf eMeO GdCfOdSj GdMGL GdTWjHj, GdTWjHj,J (B963 (3g` s
(3ChdgG (B:s
(3GdMeO ddg PcQ Cgd GdYde Cf GdOfjG cdgG SHYI Cda SfI s
(3BNQgG (B:s
(3hcGf bHd GdNdGaI jCcd GdfYe hjdHS LOjO GdKjGH , adeG hdi GdNdGaI cGf Cf jbWY LejY s
(3GdfSNI HgG MhGTs
(3GdChQGb GdNeSI GdCNjQg eSWQJgG (B39 (3SWQkGs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B292s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs